ARE AVIATION REGULATIONS EFFECTIVE IN MANAGING FOREIGN AIRCRAFT VIOLATIONS IN INDONESIA? - Aisyatus Sa'adah; Kania Rahma Nureda; Aista Wisnu Putra (Diponegoro Law Review, 2023)
Sovereignty is an essential thing for a country to maintain, and every country has exclusive jurisdiction and authority to control the air space above its territory, Indonesia is a country that has a large area, but with a large area that is owned if it is not used and maintained correctly it will become a threat to its sovereignty, as evidenced by the existence of cases of airspace violations every year, one of which is carried out by foreign aircraft in Indonesian airspace at this time. This study aims to determine how regulations or rules and law enforcement in airspace violations by foreign aircraft in Indonesia are increasing and what the causes or factors are in the increase in these violations. This is legal research with a normative perspective, a statutory approach, a conceptual approach, and interviews. The results of study explain that there are legal rules that are used in carrying out law enforcement and control of air space in Indonesia's territory. However, these rules are considered ineffective, and because the ineffectiveness of the existing rules affects law enforcement, the impact on law enforcement could be more optimal—committed for violations of foreign aircraft in the territory of Indonesia.